(untitled) (Interdisciplinary Studies Journal, 2021)
Critical Discourse Analysis (CDA) is defined as an interdisciplinary theoretical-methodological approach that serves social and human sciences as scientific support for explaining social problems related to power as a form of control (CHOULIARAKI, FAIRCLOUGH, 1999; VIEIRA, RESENDE, 2016). It also focuses on studying how social relations are asymmetrically structured in society (CHOULIARAKI; FAIRCLOUGH, 1999; FAIRCLOUGH, 1995, 2001, 2003) and develops “ways of analyzing language that address its involvement in the functioning of contemporary capitalist society” (FAIRCLOUGH, 1995, p. 01). It is within CDA that the interdisciplinary nature of language is revealed, understood as a “resource that can be used both to establish and sustain relations of domination and, conversely, to contest and overcome such issues” (VIEIRA; RESENDE, 2016, p. 15). CDA, as a critical approach, seeks to study how discourses shape and are shaped by the dynamics of social life by de-naturalizing social determinations and the effects of discourses produced and reproduced in society, and how these discourses contribute to inequality and asymmetric power relations. (FAIRCLOUGH, 1995, p. 28). In view of this, the present work systematizes the theoretical-methodological framework of CDA by determining the central concepts and principles of analysis. It is observed that, although CDA is naturally linked to Linguistics because it analyzes language as discourse, it is not limited to a single discipline, as occurs with other areas of linguistics such as Sociolinguistics and Conversation Analysis, for example (MELO, 2018, p. 26). It is a method of investigation that provides theoretical support to the problem under study.